Risk prediction of covid-19 related death and hospital admission in adults after covid-19 vaccination: national prospective cohort study - Hippisley-Cox, J; Coupland, CA; Mehta, N; Keogh, RH; Diaz-Ordaz, K; Khunti, K; Lyons, RA; Kee, F; Sheikh, A; Rahman, S; Valabhji, J; Harrison, EM; et al. (BMJ Publishing Group, 2021)
Objectives To derive and validate risk prediction algorithms to estimate the risk of covid-19 related mortality and hospital admission in UK adults after one or two doses of covid-19 vaccination.